Utilization of Aquaculture Effluent as an Organic Fertilizer to Improve Soil Fertility and Cassava (Manihot esculenta Crantz) Yield - Wira Hadianto; Nana Ariska; Taufiq; Maulidil Fajri; Nhyra Kamala Putri; Abdul Latif (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2026)
This study evaluated the potential of aquaculture effluent as a liquid organic fertilizer to enhance soil fertility and cassava (Manihot esculenta Crantz) productivity. Conducted in Blang Berandang Village, West Aceh Regency, the experiment employed a Randomized Complete Block Design (RCBD) with six treatments: a control (0% effluent), inorganic fertilizer, and four effluent concentrations (25%, 50%, 75%, and 100%), each replicated four times. Measured variables included soil chemical properties (pH, organic carbon, total nitrogen, available phosphorus, and exchangeable potassium), plant growth parameters, and tuber yield. Results indicated that the aquaculture effluent was rich in nutrients, containing 35.2 mg L⁻¹ nitrogen, 12.6 mg L⁻¹ P₂O₅, and 22.4 mg L⁻¹ K₂O, with a C/N ratio of 3.6. Effluent application significantly improved soil physicochemical properties, raising soil pH from 5.5 to 6.9 and organic carbon from 1.25% to 2.45%. Furthermore, total nitrogen, available phosphorus, and exchangeable potassium levels increased in proportion to effluent concentration. The 75% effluent treatment yielded the optimal results, producing a plant height of 135.4 cm and a tuber weight of 4.12 kg per plant—a 90% increase compared to the control. These findings demonstrate that aquaculture effluent significantly enhances soil fertility and cassava productivity relative to untreated controls. Consequently, its utilization offers a sustainable, eco-friendly strategy for integrated aquaculture–agriculture systems, contributing to increased crop production while mitigating environmental impacts associated with aquaculture waste.